Designing Green Manufacturing with OECD Method on a Micro Business Oox Guitarmaker Ambarawa - Bobbie Ardiansyah Jatmiko; Bayu Prestianto (Journal of Management and Business Environment (JMBE), 2022)
This study aims to know level and design of green manufacturing application on Oox Guitarmaker Ambarawa. The level of green manufacturing can be measured using one of the theories from The OECD titled Sustainable Manufacturing Toolkit. Three levels of green manufacturing comprises Beginner, Intermediate, and Advance. The research on design uses the theory of green manufacturing proposed by Arindam (2011) comprising of green energy, green products, and green processes. The research found that the level of green manufacturing of Oox Guitarmaker Ambarawa is an intermediate with 11 of 18 indicators that are green This research also provides results in the form of suggestions to Oox Guitarmaker Ambarawa so that they can make improvements to the indicators that are not yet green.